Behavioral activation treatment for cancer patients - Fernández, Concepción; Villoria, Erica; Amigo, Isaac; Padierna, Celina; Gracia, José Manuel; Fernández, Roberto; Peláez, Ignacio (Anales de Psicología / Annals of Psychology, 2011)
Aim: In this research was evaluated the efficacy of the behav-ioural activation therapy in patients suffering lung cancer and breast cancer along the oncologic treatment. Measures: The variables used as outcome criterion were: frequency and intensity of the illness symptoms and/o medical treatment; affectation of personal autonomy, daily life activity, leisure, work activity, family and social relationships and emotional distur-bances. Data were collected through standardized scales (IK, HAD, QLQ-C30), self-report and clinical interview in each of the treatment sessions and three months follow-up. The control group underwent the same number of sessions of assessment. The total number of participants with breast cancer was 54 (control group 29 and experimental group 25) and lung cancer 84 (control group 37 and experimental group 47. Results: The subjects of the experimental group of lung cancer showed a higher recov-ery of daily life activities and leisure and less difficulty sleeping, anxiety, depression and less loss of appetite. In the breast cancer no differences were found between groups but the effect of time was significant in the variables tiredness and fatigue. Conclusions: The patients that, during chemotherapy treatment, maintain their daily activities and leisure activities do not show emotional disturbances. The behavioural activation can contribute to improving the quality of life and prevent emotional distur-bances in cancer